The law of maritime delimitation and the Malaysian practice - Salma binti Yusof (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
Maritime delimitation is an issue of crucial importance under the law of the sea. Until now, the applicable law in maritime delimitation is not clearly established. This research, which is purely from legal perspective, analyse and examine the law governing maritime delimitation based on the International Law of the Sea Conventions, judicial decisions and maritime delimitation treaties. The main idea is to establish a comprehensive practicable delimitation methodology adaptable to all situations of maritime delimitation. Special case study is made on the Malaysia's practice on maritime delimitation dealing with its selected neighbouring states. In conducting this research descriptive, historical and critical analysis is applied. The methodology also includes semi-structured interviews with selected authorities in the field. It is submitted that the comprehensive practicable delimitation methodology is to be based on “equidistance principle” to achieve an equitable result taking into account relevant circumstances. Malaysia, being state party to the 1982 United Nations Convention on the Law of the Sea, has demonstrated a flexible and conciliatory approach towards maritime delimitation. To a certain extent, Malaysia has been successful in the conclusion of both maritime delimitation agreement and provisional arrangement pending final delimitation.